Research progress on endoplasmic reticulum homeostasis in kidney diseases - Dan Wu; Li-Feng Huang; Xiao-Cui Chen; Xiao-Rong Huang; Hui-Yuan Li; Ning AN; Ji-Xin Tang; Hua-Feng Liu; Chen Yang (Cell Death and Disease, 2023)
Abstract The endoplasmic reticulum (ER) plays important roles in biosynthetic and metabolic processes, including protein and lipid synthesis, Ca2+ homeostasis regulation, and subcellular organelle crosstalk. Dysregulation of ER homeostasis can cause toxic protein accumulation, lipid accumulation, and Ca2+ homeostasis disturbance, leading to cell injury and even death. Accumulating evidence indicates that the dysregulation of ER homeostasis promotes the onset and progression of kidney diseases. However, maintaining ER homeostasis through unfolded protein response, ER-associated protein degradation, autophagy or ER-phagy, and crosstalk with other organelles may be potential therapeutic strategies for kidney disorders. In this review, we summarize the recent research progress on the relationship and molecular mechanisms of ER dysfunction in kidney pathologies. In addition, the endogenous protective strategies for ER homeostasis and their potential application for kidney diseases have been discussed.